Real-time, in situ, atomic scale observation of soot oxidation. (April 2019) - Toth, Pal; Jacobsson, Daniel; Ek, Martin; Wiinikka, Henrik
Abstract: The oxidation of soot is a complex process due to the heterogeneous structure of the material. Several mechanisms have been hypothesized based on ex situ studies, but need confirmation from in situ observation; furthermore, deeper insight is needed to develop and validate structure-dependent reaction mechanisms. In this work, soot oxidation was for the first time observed at atomic scale in situ, in real-time, using a spherical aberration-corrected Environmental Transmission Electron Microscope. The transformation of individual soot particles was followed through from initiation to complete conversion. Observations clearly showed the existence of different burning modes and particle fragmentation previously hypothesized in the literature. Furthermore, transitioning between the modes—affected by temperature and O2 pressure—was unambiguously observed, explaining previous observations regarding structure-dependent and time-varying oxidation rates. A new mode of burning in which oxidation happens rapidly in the bulk phase with the disruption of long-range lamellar order was observed and is suspected to be dominant at practically relevant conditions. The ability to unambiguously relate different burning modes in terms of nanostructure will be of importance for optimizing both soot emission abatement and properties of nanoparticulate carbon products. Graphical abstract: Image 1